THE ABILITY OF GROSS PROFIT, OPERATING PROFIT, NET PROFIT, AND WORKING CAPITAL IN PREDICTING FUTURE CASH FLOWS (Empirical Study of Companies Listed in the Jakarta Islamic Index) - Ainiyah, Ghonimah Zumroatun; Permatasari, Kartika Dewi; Qurrotuaini, Dhiya Nisrina; Widodo, Untung (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
Users of financial statements make forecasts regarding the future situation of the entity in order to anticipate opportunities and identify potential risks. Gross profit, operating profit, net profit, and working capital are important pieces of information for investors because they allow for the prediction of future cash flows. However, for companies listed on the Jakarta Islamic Index, there is instability in gross profit, operating profit, net profit, and working capital, which leads to changes in cash flow. The research is of an associative quantitative nature, with a research population consisting of 50 companies listed on the Jakarta Islamic Index from 2019 to 2022. By using a purposive sampling technique, a sample of 24 companies was obtained, resulting in a total sample size of 96 samples over the span of 4 years. The data used is secondary data, collected through the official IDX website at www.idx.co.id. The analytical method employed is multiple linear regression. The findings of the study indicate that gross profit and working capital have a significant impact on the ability to predict future cash flows. However, operating profit and net profit do not possess the same predictive power. Furthermore, the study reveals that gross profit, operating profit, net profit, and working capital collectively contribute to the prediction of future cash flows with an impressive explanatory power of 89.3%. Keywords: gross profit, operating profit, net profit, working capital, future cash flow